PENERAPAN HAK INGKAR NOTARIS SEBAGAI SAKSI DALAM PERADILAN PIDANA (Studi Putusan Nomor 685/Pid.B/2016/Pn.Mlg) - Hika Deriya Fajar Rizki Asril Putra, (The Juris, 2022)
The Right of Denial can be carried out with restrictions as long as the Notary is examined by an agency requesting information or information from the Notary regarding a deed that has been or was drawn up by or before the Notary concerned. Considering that a Notary basically only records what the witnesses say and is not required to investigate the material truth of its contents. legal implications for the default of Notary rights based on Article 16 paragraph (1) letter f of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of a Notary if the Notary is a witness in a criminal court.